Pemberdayaan Petani Sawit Rakyat Melalui Enterpreneurship Intercropping Tanaman Edamame Guna Peningkatan Perekonomian Desa Silomlom Menuju Sustainability In Green Economy: Pengabdian - Marzuti Isra; Purjianto; Hari Gunawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Oil palm is a strategic commodity that serves as the main livelihood for rural communities; however, smallholder oil palm farmers continue to face low income levels, particularly during the immature phase of oil palm cultivation, which lasts for 3–4 years. This condition highlights the need for adaptive farming strategies that can generate short-term income without disrupting the main crop. This community service program aimed to empower smallholder oil palm farmers through the implementation of an entrepreneurship-based intercropping system using edamame to increase farmers’ income and strengthen sustainable rural economic development. A participatory approach was employed, actively involving farmers in all stages of the program, including situation analysis, training and extension activities, implementation of edamame intercropping demonstration plots, and evaluation through focus group discussions. The program was implemented on approximately 1,000 m² of smallholder oil palm land using edamame as an intercrop. The results indicate that edamame intercropping effectively optimizes the use of inter-row spaces in oil palm plantations, provides additional short-term income due to its short harvesting period, and enhances farmers’ knowledge and skills in crop management, business management, and digital-based marketing.